(untitled) (Research, Society and Development, 2023)
Plastic fragments, more specifically microplastics (MPS) and nanoplastics (NPS) are present and produced in large quantities and on global scales. They are found virtually everywhere in seawater, food and air. Thus, considering the forms of human contact such as consumption itself or breathing and biological effects, chemical effects of these fragments, it becomes necessary to discuss the relevance and possible effects of this material on the individuals’ bodies. This study aims to understand the possible relationship between harmful effects to the body related to contact with such plastic fragments, observing their effects. Using the integrative exploratory literature review, 22 articles were used, with eight articles being excluded due to non-compliance with the inclusion criteria. The consumption of MPS and NPS can induce harmful effects on organisms either through physical, chemical or biological phenomena. In the first, there is an association with physical barriers that induce inflammation processes. The biological role addresses the association of MPS with some possibly pathogenic beings to humans. Finally, the chemical role related to the phenomenon of adsorption of harmful proves to be a generation of possible harm. Therefore, it is essential to carry out new studies on the effects of MPS and NPS in human, due to their high coverage on a worldwide scale and the report that, although there are few studies carried out recently, they present alarming pictures about the action harmful of these compounds to humans.